1993
DOI: 10.1128/jb.175.9.2734-2742.1993
|View full text |Cite
|
Sign up to set email alerts
|

Low-molecular-weight thiols in streptomycetes and their potential role as antioxidants

Abstract: The intracellular low-molecular-weight thiols present in five gram-positive Streptomyces species and one Flavobacterium species were analyzed by high-performance liquid chromatography after fluorescence labeling with monobromobimane. Bacteria were chosen to include penicillin and cephalosporin 13-lactam producers and nonproducers. No significant amount of glutathione was found in any of the streptomycetes. Major intracellular thiols in all strains examined were cysteine, coenzyme A, sulfide, thiosulfate, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
78
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 34 publications
2
78
0
Order By: Relevance
“…However, genes with similarity to gshB have until now not been observed in Gram-positives (see also Copley and Dhillon 2002). The assignment of a function to the corresponding Îł-GCS-like hypothetical proteins is uncertain, particularly because these organisms are not known to synthesise GSH (Newton et al 1993(Newton et al , 1996. These observations do suggest that Gram-positive bacteria generally lack the capability to synthesise glutathione, although some strains are able to import glutathione from the environment (Sherrill and Fahey 1998).…”
Section: Introductionmentioning
confidence: 99%
“…However, genes with similarity to gshB have until now not been observed in Gram-positives (see also Copley and Dhillon 2002). The assignment of a function to the corresponding Îł-GCS-like hypothetical proteins is uncertain, particularly because these organisms are not known to synthesise GSH (Newton et al 1993(Newton et al , 1996. These observations do suggest that Gram-positive bacteria generally lack the capability to synthesise glutathione, although some strains are able to import glutathione from the environment (Sherrill and Fahey 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the bacterial prokaryotic group termed actinomycetes lack the low molecular weight thiol, glutathione, typically found in many bacteria and in eukaryotes and instead produce mycothiol (acetyl-Lcysteine-1-D-myo-inosityl-2-deoxy-D-glucopyranoside) (1,2). Similar to glutathione, mycothiol provides the cell protection from oxidative damage and electrophilic toxins (3,4) and is maintained in the reduced state by a reductase (5).…”
mentioning
confidence: 99%
“…Mycothiol biosynthesis in M. tuberculosis is a multistep process involving four enzymatic reactions catalyzed by MshA, MshB, MshC, and MshD (Scheme 1). Mycothiol synthase (MshD), 2 the last enzyme in mycothiol biosynthesis, catalyzes the acetylation of the cysteinyl amine of 1-D-myo-inosityl-2-L-cysteinylamido-2-deoxy-␣-D-glucopyranoside (desacetylmycothiol (DAM)) (9). The close proximity of the relatively reactive primary amine to the active thiol would potentially yield side reactions during mycothiol reduction and conjugation reactions, thus preventing mycothiol regeneration by mycothione reductase or mycothiol S-conjugate amidase.…”
mentioning
confidence: 99%
“…Because ACV structurally resembles glutathione, y-glutamyl-cysteinyl-glycine, the most common intracellular lowmolecular-weight thiol, we reasoned that the S. clavuligerus disulfide reductase might be related to glutathione reductase. However, extensive analysis of cell extracts of streptomycetes revealed that they lack glutathione (30) and glutathione reductase (2). Moreover, biochemical characterization of the S. clavuligerus reductase showed that, in contrast to glutathione reductase, it reduces a wide range of disulfides in low-molecular-weight compounds, is a potent reductant of disulfide bonds in proteins, and is composed of two nonidentical polypeptides.…”
mentioning
confidence: 99%